Using Geographic Information Systems (GIS) Program and Water Quality Index (WQI) to Assess and Manage Groundwater Quality in the City of Baghdad - Jassim Mohammed Alwaeli; Sura Kareem Ali; Athraa Hashim Mohammed (Journal of Engineering, 2021)
Groundwater is an essential source because of its high quality and continuous availability characterize this water resource. Therefore, the study of groundwater has required more attention. The present study aims to assess and manage groundwater quality's suitability for various purposes through the Geographical Information System GIS and the Water Quality Index WQI. The study area is located in the city of Baghdad in central Iraq, with an approximate area of ​​900 , data were collected from the relevant official departments representing the locations of 97 wells of groundwater in the study area for the year 2019, as it included physicochemical parameters such as  pH, EC, TDS, Na, K, Mg, Ca, Cl,  , and  . It used (kriging method) in the geographic information system to generate the groundwater physical and chemical parameters' spatial distribution and the water quality index map. To estimate the water quality index, ten parameters were considered  pH, TDS, Na, K, Mg, Ca, Cl,  ,  , and  . The estimated WQI value for groundwater samples in the study area ranges from 50 to 300. Based on the analysis, most of the area under study falls approximately 70% in poor water class and 30% in good water class, where the distribution of the groundwater samples with respect to their quality classes such as excellent, good, poor, very poor and unfit for human drinking purpose, was found to be 3 %, 30 %, 33 %,  12 %, and 20 %, respectively.